PENGARUH PENGENDALIAN INTERNAL DAN MORALITAS INDIVIDU PADA KECENDERUNGAN KECURANGAN AKUNTANSI - Udayani, Anak Agung K. Finty; Ratna Sari, Maria M (E-Jurnal Akuntansi, 2017)
This research aimed to determine the effect of internal control and individual morality to the tendency of accounting fraud. The theory used in this research are the Agency Theory and Theory Of Planned Behavior. The population in this study is staff accounting department Umalas villa. This study using purposive sampling technique. These samples were taken are as many as 34 staff accounting. The Collected data using by questionnaires. The data analysis technique used in this research is multiple linear regression. The results of this research showed that the internal control and individual morality have negatively affect of tendency of the accounting fraud at the villa in Umalas area.
Keywords: internal control; individual morality; the tendency of accounting fraud